Research on coordinated control of hydro-mechanical continuously variable transmission tractor mode switching based on model reference adaptation - Xu, Liyou; Zhang, Linkuan; Wang, Dongqing; Liu, Mengnan; Zhang, Junjiang (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The difference between the speed of the hydraulic speed control system and the mechanical transmission speed is too large during the mode-switching process of the equipped HMCVT tractor, which leads to the deterioration of the smoothness of the mode-switching process. The paper proposes a mode-switching coordination control strategy based on the adaptive model reference. Based on the mode-switching process, the mathematical model of HMCVT mode-switching is constructed. With the output speed of the hydraulic system as the reference model, the output speed of the mechanical transmission as the control object, and the output speed of the mechanical transmission following the output speed of the hydraulic system as the target, the design model reference adaptive controller, based on the MATLAB simulation platform for the simulation test of the control strategy is presented. The results show that when switching from H mode to HM1 mode, the maximum jerk is reduced by 70.3% and the slip friction work is reduced by 28.6%, and when switching from HM1 mode to H mode, the maximum jerk is reduced by 67% and the slip friction work is reduced by 28.9% compared to the use of the rule-based control strategy.